Exploring IL-1β and IL-17 in Periodontitis-Associated Oral Aging Pathways - Ria Aryani Hayuningtyas; Sheila Soesanto; Jessica Endriyana (SONDE (Sound of Dentistry), 2024)
Introduction: Periodontitis, a severe stage of periodontal disease marked by chronic and irreversible inflammation, is linked to a complex cytokine network. This persistent inflammation leads to significant genomic damage and the emergence of senescent phenotypes in oral tissues. This study aims to explore the role of interleukin-1β (IL-1β) and interleukin-17 (IL-17) in inducing oral senescence associated with periodontitis, particularly focusing on their contribution to the Senescence-Associated Secretory Phenotype (SASP). Methods: A thorough literature review was conducted via the MEDLINE database on PubMed, covering records up to 2018. Studies involving periodontitis patients formed the experimental group, while those on individuals with healthy periodontal conditions were the controls. Relevant in vitro studies on SASP were also included. Results and discussion: The results showed a significant increase in IL-1β and IL-17 secretion in periodontitis patients compared to those with healthy tissues. In vitro studies confirmed that these cytokines directly induce the secretion of SASP components, including SA‑β‑gal, p21, p53, plasminogen activator inhibitor-1 (PAI-1), and p16. These findings suggest that IL-1β and IL-17 play a critical role in promoting cellular senescence in periodontal tissues by inducing SASP. Conclusion: This study highlights IL-1β and IL-17 as key mediators in oral senescence within the context of periodontitis. Their excessive production contributes to SASP, leading to cellular senescence in periodontal tissues. Understanding these mechanisms is crucial for developing targeted therapies to mitigate the detrimental effects of chronic periodontitis on oral health.